Assessment of Knowledge among Nepalese Web Users about COVID-19 - Siddiqui, Saharoj; Shrewastwa, Mukesh Kumar; Pandey, Aashish; Shukla, Ambalika; Yadav, Santosh (Journal of Nepalgunj Medical College, 2022)
Introduction: Coronavirus disease 2019 is a highly pestilent global pandemic caused by severe acute respiratory syndrome coronavirus 2, destroying various walks of human life where the only ray of light coming through can be seen in the form of the vaccine. Nepal, having limited resources and vaccine doses, is distributing them based on immediate requirements. One’s right attitude and practices toward the current issue determined by their knowledge and awareness is the need of the hour. Awareness and right knowledge about the magnitude of damage this disease can cause, the methods of its spread,  the incubation period, and the right time to seek medical help can make people conscious and adopt preventive practices which can be life-saving for themselves as well as the society in a time when the vaccine is not available for all.Aims: To assess the knowledge Among Nepalese web users about COVID-19 Methods: A descriptive web-based cross-sectional survey was conducted among the 464 web users of Nepal.Results: Out of 464 participants, there were 143 male per 100 females. The average knowledge score observed in females was 75.4% whereas for male was 73.2%. The average knowledge score of people of age below 18 years, 18-30 years, 30-60 years, and above 60 years was 45.83%, 75.39%, 67.73%, and 69.06% respectively. It was 73.33% in the postgraduates, 76.8% in the graduates, and 59.48% in the illiterates.Conclusion: The Nepalese web users were knowledgeable about COVID-19. Females had more knowledge about COVID-19 than males. People in the age group 18 to 30 years were more knowledgeable compared to other age groups.